Incidence of retinoblastoma in children and adolescents in Brazil: A population-based study - Barbosa, Annamaria Ciminelli; de Magalhães-Barbosa, Maria Clara; Moreira, Jessica Pronestino de Lima; Colombini, Giovanni Nicola Umberto Italiano; Prata-Barbosa, Arnaldo (Frontiers in Pediatrics, 2022)
Objective: To estimate the incidence of retinoblastoma in children and adolescents in Brazil based on Population-Based Cancer Registry (PBCR), describing temporal trends and some quality indicators of this registry. Methods: Based on secondary data from the PBCR of the National Institute of Cancer (INCA) (2000-2018), by selecting the morphological code of retinoblastoma, the annual incidences per million (0-19 years of age) in each local PBCR were estimated by sex and age group, global combined and by region, in addition to the percentage of diagnosis only by death certificate (DC) or not informed (NI), and the male/female ratio (M/F). An annual incidence trend in the five Brazilian geographic regions was also analyzed using the inflection point regression technique. Results: 675 patients were identified in 28 PBCR, 91% between 0-4 years of age. The overall combined incidence per million by age group was: 7.02 (0-4 y/o), ranging from 5.25 in the Midwest to 11.26 in the Northeast; 0.46 (5-9 y/o); 0.05 (10-14 y/o) and 0.03 (15-19 y/o). The combined incidence per million, adjusted for the world population, was 2.23 (0-14 y/o) and 2.24 (0-19 y/o). The DC and NI percentages were 13% and 18%, respectively; the M/F ratio was 1.3. The incidence remained stable throughout the study period, except for the city of São Paulo, where there was a significant reduction of 3.4% per year. Conclusions: In Brazil, except for the Northeast region, the incidences of retinoblastoma were lower than those reported in several countries worldwide, suggesting possible underreporting, and the time series analysis showed a stable trend. Although this pioneering study brings a recent panel of available data on retinoblastoma in Brazil, more precise estimates are needed and welcome for better planning of onco-ophthalmologic care in the country.